Law 101 : everything you need to know about American law - Feinman, Jay M. (New York, NY : Oxford University Press, 2018)
"In this fifth edition of his bestselling classic, Jay Feinman provides an authoritative and up-to-date overview of the American legal system. The book covers all the main subjects taught in the first year of law school, and discusses every facet of the American legal tradition, including constitutional law, the litigation process, and criminal, property, and contracts law. Above all, Feinman reveals to readers of all kinds that despite its complexities and quirks, the law can be understood by everyone"--
There are no secret books : you can understand the law -- The supreme law of the land : constitutional law -- First freedoms : constitutional rights -- Your day in court : the litigation process -- Hot coffee and crashing cars: Tort Law -- A deal's a deal : contract law -- You are what you own : property law --Crime doesn't pay : criminal law -- Protecting the innocent, freeing the guilty : criminal procedure.
Includes indexes.
Keywords: Law -- United States -- Popular works; LAW / General; LAW / Administrative Law & Regulatory Practice; LAW / Constitutional